Diabetes, subclinical atherosclerosis and multiple cardiovascular risk factors in hard-to-reach asymptomatic patients. (November 2018) - Mamudu, Hadii M; Alamian, Arsham; Paul, Timir; Subedi, Pooja; Wang, Liang; Jones, Antwan; Alamin, Ali E; Stewart, David; Blackwell, Gerald; Budoff, Matthew
Aim: To examine the association of cardiovascular disease risk factors with and their cumulative effect on coronary artery calcium in hard-to-reach asymptomatic patients with diabetes. Methods: A total of 2563 community-dwelling asymptomatic subjects from Central Appalachia participated in coronary artery calcium screening at a heart centre. Binary variable was used to indicate that coronary artery calcium was either present or absent. Independent variables consisted of demographic and modifiable risk factors and medical conditions. Descriptive statistics and multinomial logistic regression analyses were conducted. Results: In total, 55.8% and 13.7% of study participants had subclinical atherosclerosis (coronary artery calcium ⩾1) and diabetes, respectively. The presence of coronary artery calcium was higher in subjects with diabetes (68.5%) than those without (53.8%). Compared to subjects without diabetes with coronary artery calcium = 0, obesity, hypertension, hypercholesterolaemia and smoking increased the odds of the presence of coronary artery calcium (coronary artery calcium score ⩾1) regardless of diabetes status; however, with larger odds ratios in subjects with diabetes. Compared to subjects without diabetes with coronary artery calcium score = 0, having 3, 4 and ⩾5 risk factors increased the odds of presence of coronary artery calcium in subjects with diabetes by 14.06 (confidence interval = 3.26–62.69), 32.30 (confidence interval = 7.41–140.82) and 47.12 (confidence interval = 10.35–214.66) times, respectively. Conclusion: There is a need for awareness about subclinical atherosclerosis in patients with diabetes and more research about coronary artery calcium in subpopulations of patients.